Comparison of international approaches to sustainable remediation. (15th December 2016) - Rizzo, Erika; Bardos, Paul; Pizzol, Lisa; Critto, Andrea; Giubilato, Elisa; Marcomini, Antonio; Albano, Claudio; Darmendrail, Dominique; Döberl, Gernot; Harclerode, Melissa; Harries, Nicola; Nathanail, Paul; et al.
Abstract: Since mid-to-late 2000s growing interest for sustainable remediation has emerged in initiatives from several international and national organisations as well as other initiatives from networks and forums. This reflects a realisation that risk-management activities can about bring environmental, social, and economic impacts (positive or negative) in addition to achieving risk-based remediation goals. These ideas have begun to develop as a new discipline of "sustainable remediation". The various initiatives have now published a number of frameworks, standards, white papers, road maps and operative guidelines. The similarities and differences in the approaches by these outputs and general trends have been identified. The comparison is based on a set of criteria developed in discussion with members of these various initiatives, and identifies a range of similarities between their publications. Overall the comparison demonstrates a high level of consensus across definitions and principles, which leads to the conclusion that there is a shared understanding of what sustainable remediation is both across countries and stakeholder groups. Publications do differ in points of detail, in particular about the operational aspects of sustainable remediation assessment. These differences likely result from differences in context and legal framework. As this analysis was carried out its findings were debated with members of the various international initiatives, many of whom have been included as authors. Hence the outcomes described in this paper can be seen as the result of a sort of multi-level debate among international experts (authors) and so can offer a starting point to new sustainable remediation initiatives (for example in other countries) that aim to start developing their own documents. Highlights: International frameworks for implementing sustainable remediation are collated. Sustainable remediation frameworks from around the world are compared. An international approach for a joint view on sustainable remediation is proposed.